Counseling on the Making of the Innovative Herbal Drink "GoldenBlend Tonic" in an Effort to Empower Women Farmers in Gelam Village, Candi, Sidoarjo - Maharani, Sephia; Wijaya, Nasywa Aulia; Damayanti, Tiara; Winanda, Nadia Ayu; Setiawan, Risqi Firdaus (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2024)
Empowerment of Women Farmers Group (KWT) must be done so that local potential can be utilized and agricultural products can be processed into high-value economic products. One of the local potentials that can be developed is Family Medicinal Plants (TOGA). Besides being beneficial for health, TOGA also has high economic value when sold as raw materials for traditional medicine and instant herbal drinks. The empowerment effort carried out is counseling on making the innovative herbal drink GoldenBlend Tonic, a combination of high-quality spices. Community Service activities were carried out at the Gelam Village Hall, Candi District, Sidoarjo, attended by 25 people from the Gelam Village KWT. This activity aims to empower the local women farmers by providing knowledge and skills in processing agricultural products into high-value economic products. The method used is counseling involving presentations, discussions, and direct practice. The result of this activity is an increased understanding and skills of the KWT regarding innovative herbal drink products. In the future, it is expected that the Gelam Village KWT can develop new products, increase productivity, and strengthen the economy of their families and communities.